Role of oxidative stress in the relationship between periodontitis and systemic diseases - Shang, Jiaxin; Liu, Haifeng; Zheng, Youli; Zhang, Zheng (Frontiers in Physiology, 2023)
Periodontitis is a common inflammatory disease. It is characterized by destruction of the supporting structures of the teeth and could lead to tooth loss and systemic inflammation. Bacteria in inflamed gingival tissue and virulence factors are capable of entering the bloodstream to induce systemic inflammatory response, thus influencing the pathological process of many diseases, such as cardiovascular diseases, diabetes, chronic kidney disease, as well as liver injury. An increasing body of evidence show the complex interplay between oxidative stress and inflammation in disease pathogenesis. When periodontitis occurs, increased reactive oxygen species accumulation leads to oxidative stress. Oxidative stress contributes to major cellular components damage, including DNA, proteins, and lipids. In this article, the focus will be on oxidative stress in periodontal disease, the relationship between periodontitis and systemic inflammation, and the impact of periodontal therapy on oxidative stress parameters.